1998
DOI: 10.1074/jbc.273.6.3291
|View full text |Cite
|
Sign up to set email alerts
|

Different Endosomal Proteolysis Requirements for Antigen Processing of Two T-cell Epitopes of the M5 Protein from ViableStreptococcus pyogenes

Abstract: We studied endosomal proteolysis of the surface fibrillar M5 protein from viable Streptococcus pyogenes as an essential step involved in major histocompatibility complex class II-restricted antigen processing of two immunodominant CD4؉ T-cell epitopes (17-31/E d and 308 -319/ A d ). Intracellular proteolysis of viable streptococci for presentation of 17-31, bound by serine proteinase cleavage sites, was mediated by serine proteinases, whereas processing of soluble recombinant M5 protein required in addition cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Second, the intracellular processing of CII for presentation of the glycosylated epitope was more sensitive than the nonglycosylated epitope to treatment of macrophages with inhibitors of cysteine proteinases, aspartic proteinases, and metalloproteinases, which is consistent with the interpretation that CII was differentially processed for presentation of the glycosylated and nonglycosylated epitopes. In addition, both forms of the epitope were profoundly sensitive to inhibitors of serine proteinases, which together with the results of our previous study (30), suggests a major role of this class of enzyme in antigen processing.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Second, the intracellular processing of CII for presentation of the glycosylated epitope was more sensitive than the nonglycosylated epitope to treatment of macrophages with inhibitors of cysteine proteinases, aspartic proteinases, and metalloproteinases, which is consistent with the interpretation that CII was differentially processed for presentation of the glycosylated and nonglycosylated epitopes. In addition, both forms of the epitope were profoundly sensitive to inhibitors of serine proteinases, which together with the results of our previous study (30), suggests a major role of this class of enzyme in antigen processing.…”
Section: Discussionsupporting
confidence: 51%
“…Adherent macrophages (10 5 /well) in 48-well flat-bottomed plates were pulsed with 20 g/ml of CII for 3 hours in the absence or presence of the enzyme inhibitors pepstatin (0.5 mM) (28), phenanthroline (0.1 mM) (29), phenylmethylsulfonyl fluoride (PMSF; 3.0 mM), 20 mM NH 4 Cl (30), (2S,3S)-trans-epoxysuccinyl-Lleucylamido-3-methylbutane ethyl ester (E-64d; 10 M) (31), N␣-p-tosyl-L-lysine chloromethylketone (TLCK; 250 M) (32), and N-p-tosyl-L-phenylalanine chloromethylketone (TPCK; 2.5 M) (29), with either cycloheximide (20 M) to block protein synthesis (33) or brefeldin A (1.0 g/ml) to disrupt Golgi transport (34). The optimal doses of inhibitors were established in separate dose-response experiments, as reported previously (30).…”
Section: Methodsmentioning
confidence: 99%
“…The difference in the repertoire of the T cell responses that we observed as a result of this distinct Ag targeting is consistent with previous reports. Streptococcus protein Ags have been shown to require different proteases for processing and presentation of two epitopes (59), and the Ag uptake mechanism influences their presentation by determining which subcellular compartment is targeted (60). It was also reported that association of lymphocytic choriomeningitis virus minigene epitopes with another member of the LAMP protein family, lysosomal integral membrane protein II, increased the CD4 ϩ response to one epitope but decreased another, suggesting that different Ag processing pathways can indeed influence on the priming of a T cell response to a specific Ag (61).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of APC with some inhibitors of serine proteinase activity was shown to have a limited effect on presentation of epitopes of sperm whale myoglobin (34) or hen egg lysozyme (35). However, we have demonstrated sensitivity of presentation of T-cell epitopes of the surface M protein of Streptococcus pyogenes to the chloromethyl ketones TLCK and TPCK (36), and here we have used the more effective and inclusive broad spectrum serine proteinase inhibitor DCI to implicate this enzyme family in antigen processing.…”
Section: Fig 2 the Kinetics Of Presentation Of Cd4mentioning
confidence: 99%